Get training or wait? Long-run employment effects of training programs for the unemployed in West Germany - Bernd Fitzenberger; Aderonke Osikominu; Robert Völter (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
Long-term public sector sponsored training programs often show little or negative short-run employment effects and often it is not possible to assess whether positive long-run effects exist. Based on unique administrative data, this paper estimates the longrun differential employment effects of three different types of training programs in West Germany. We use inflows into unemployment for the years 1986/87 and 1993/94 and apply local linear matching based on the estimated propensity score to estimate the effects of training programs starting during 1 to 2, 3 to 4, and 5 to 8 quarters of unemployment. The results show a negative lock-in effect for the period right after the beginning of the program and significantly positive treatment effects on employment rates in the medium- and long-run. The differential effects of the three programs compared to one another are mainly driven by differences in the length of the lock-in periods.
Keywords: C14; J68; H43; 330; Wirkungsforschung; Arbeitsmarktpolitik - Erfolgskontrolle; Übungsfirma; Trainingsmaßnahme; Berufsbildung; Umschulung; Weiterbildung; Beschäftigungseffekte; Teilnehmer; Arbeitslose; berufliche Reintegration; IAB-Leistungsempfängerhistorik; IAB-Beschäftigtenstichprobe; Lock-in-Effekte; Westdeutschland; Bundesrepublik Deutschland; Arbeitsmarktpolitik; Weiterbildung; Wirtschaftspolitische Wirkungsanalyse; Arbeitslosigkeit; Schätzung; Deutschland